2013
DOI: 10.7556/jaoa.2013.036
|View full text |Cite
|
Sign up to set email alerts
|

The 2012-2013 Influenza Epidemic and the Role of Osteopathic Manipulative Medicine

Abstract: The 2012-2013 influenza epidemic arrived approximately 4 weeks early, augmented by an unusual variant type-A ("swine flu") strain that caused greater-than-normal illness and a lack of efficacy in vaccination against it. Tens of thousands of people die of influenza or related complications during a nonepidemic influenza season. Osteopathic medicine can substantially help to address the complications that result from influenza. For example, during the deadly 1918-1919 Spanish influenza pandemic, osteopaths reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…10 Although contemporary osteopathic physicians advocate influenza vaccination, antivirals, and chemoprophylaxis, they also continue to use OMT, such as lymphatic pump techniques, when treating patients with influenza. 20 Lymphatic pump techniques directly or indirectly manipulate the lymphatic system by milking lymphatic glands, releasing fascial strain around lymphatic glands, and applying gentle manual vibrations to the spleen, liver, thorax, or feet (using the legs as levers to rock the body, Figure 2 ). 4 , 21 Similar techniques are also used as an adjunct in treating asthma, postoperative atelectasis, and pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although contemporary osteopathic physicians advocate influenza vaccination, antivirals, and chemoprophylaxis, they also continue to use OMT, such as lymphatic pump techniques, when treating patients with influenza. 20 Lymphatic pump techniques directly or indirectly manipulate the lymphatic system by milking lymphatic glands, releasing fascial strain around lymphatic glands, and applying gentle manual vibrations to the spleen, liver, thorax, or feet (using the legs as levers to rock the body, Figure 2 ). 4 , 21 Similar techniques are also used as an adjunct in treating asthma, postoperative atelectasis, and pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…5 [30]. However, the evidence for this claim seems to be an article from the January 1920 Journal of the American Osteopathic Association, reprinted in the May 2013 edition [31]. This paper claimed that patients with influenza or pneumonia attended by osteopaths died at 1/40th the rate of those attended by medical doctors.…”
Section: Information From Chiropractorsmentioning
confidence: 99%
“…Four CCEs are tasked with accrediting chiropractic programs within their respective geographical region. However, the standards and processes of these CCEs are not internationally homogeneous and concerns have been raised about some accredited chiropractic programs and the subsequent practice patterns demonstrated by their graduates [12,13,[30][31][32][33]. Further, some CCEs have created a" big tent" approach to their accreditation standards and processes, resulting in all types of understanding of the term chiropractic [21,22].…”
Section: The Role Of Accrediting Agenciesmentioning
confidence: 99%
“…Osteopathic manipulative treatment (OMT) is the foundational therapy in osteopathy and has a long history of reported efficacy for a variety of conditions [ [5] , [6] , [7] , [8] ], including as adjunctive therapy for respiratory disease [ [9] , [10] , [11] ]. During the Spanish influenza pandemic of 1918–1919, osteopaths reported better outcomes than did allopaths [ [12] , [13] , [14] , [15] ]. While those reports are controversial [ 12 , 14 ], they document a history of use.…”
Section: Introductionmentioning
confidence: 99%
“…During the Spanish influenza pandemic of 1918–1919, osteopaths reported better outcomes than did allopaths [ [12] , [13] , [14] , [15] ]. While those reports are controversial [ 12 , 14 ], they document a history of use. However, comparative effectiveness studies for OMT often lag behind reported efficacy [ 4 ], and OMT for respiratory distress follows this pattern.…”
Section: Introductionmentioning
confidence: 99%